Li7La3Zr2O12 solid electrolyte sintered by the ultrafast high-temperature method. Issue 12 (September 2021) - Ihrig, Martin; Mishra, Tarini Prasad; Scheld, Walter Sebastian; Häuschen, Grit; Rheinheimer, Wolfgang; Bram, Martin; Finsterbusch, Martin; Guillon, Olivier
Abstract: All-solid-state Li batteries (ASSLBs) are regarded as the systems of choice for future electrochemical energy storage. Particularly, the garnet Li7 La3 Zr2 O12 (LLZO) is one of the most promising solid electrolytes due to its stability against Li metal. However, its integration into ASSLBs is challenging due to high temperature and long dwell time required for sintering. Advanced sintering techniques, such as Ultrafast High-temperature Sintering, have shown to significantly increase the sintering rate. Direct contact to graphite heaters allows sintering of LLZO within 10 s due to extremely high heating rates (up to 10 4 K min −1 ) and temperatures up to 1500 °C to a density around 80 %. The LLZO sintered in vacuum and Ar atmosphere has good mechanical stability and high phase purity, but kinetic de-mixing at the grain boundaries was observed. Nevertheless, the Li-ion conductivity of 1 mS cm −1 at 80 °C was comparable to conventional sintering, but lower than for Field-Assisted Sintering Technique/Spark Plasma Sintering.